Evaluation of the Implementation of APIP Inspectorate General of the Kemendikbudristek Roles in Risk Management of Y Social Aid Program - Wahyu Kartika Wijayanti; Dyah Setyaningrum (E-Jurnal Akuntansi, 2025)
This research is conducted to evaluate the implementation the role of the Kemendikbudristek Government Internal Supervisory Apparatus (APIP) in the implementation of risk management for the Y Social Aid Program. The research was conducted using a qualitative method with a case study approach on the supervisory activities of APIP in the Y Social Aid Program from 2021 to 2024. Research data was collected through questionnaires, interviews, and document reviews, and then evaluated based on relevant regulations on risk management applicable in government institutions. The results showed that the Kemendikbudristek's APIP has not adequately performed its role in Y Social Aid Program risk management, and has not been able to provide a sufficient assurance on the implementation of risk management. Research on the implementation of the APIP's role in risk management in overseeing government social assistance programs is still rare, and thus can contribute to the risk management of government social assistance programs.